The Efficacy of PTH and Abaloparatide to Counteract Immobilization-Induced Osteopenia Is in General Similar - Brent, Mikkel Bo; Thomsen, Jesper Skovhus; Brüel, Annemarie (Frontiers in Endocrinology, 2020)
Immobilization results in a substantial bone loss and increased fracture risk. Powerful bone anabolic therapies are necessary to counteract the bone loss and reduce fracture risk during periods with immobilization. Intermittent parathyroid hormone 1−34 (PTH) (teriparatide) and PTH related peptide analog abaloparatide (ABL) are potent bone anabolic therapies acting through the same receptor, but induce different durations of signaling response. We investigated the efficacy of PTH or ABL in preventing immobilization-induced bone loss in rats in a direct mole-to-mole comparison. Immobilization was achieved by injecting botulinum toxin type A (BTX) into the right hindlimb musculature. Sixty 14-week-old female Wistar rats were allocated to the following groups: Baseline, Control, BTX, BTX + PTH (80 μg/kg/day), and BTX + ABL (77 μg/kg/day). Immobilization resulted in a substantial and significant reduction in bone mineral density (aBMD), metaphyseal and epiphyseal trabecular bone volume fraction (BV/TV) and trabecular thickness (Tb.Th), metaphyseal trabecular number (Tb.N), and femoral neck bone strength. Both PTH and ABL prevented the immobilization-induced decrease in aBMD, metaphyseal and epiphyseal Tb.Th, and metaphyseal Tb.N. In addition, PTH rescued the reduction in metaphyseal BV/TV and femoral neck strength, while ABL did not. However, the effect of PTH and ABL did not differ significantly for serum calcium, aBMD, metaphyseal and epiphyseal BV/TV, Tb.Th, or Tb.N. In conclusion, in a mole-to-mole comparison the efficacy of PTH and ABL is similar in counteracting immobilization-induced reduction in bone mineral density, deterioration in trabecular microarchitecture, and decrease in bone strength.